A detailed description and 16-year validation of a new suturing method for stabilizing connective tissue grafts at recipient sites for root coverage and gingival augmentation - Om Nemichand Baghele (Wolters Kluwer Medknow Publications, 2019)
Background: Which are the different ways of stabilizing connective tissue grafts (CTGs) for root coverage and gingival augmentation by means of placement of sutures? There are various defined and undefined ways of stabilizing CTGs depending on experience and personal preferences. Most of the techniques profess use of absorbable sutures in separate interrupted fashion (sutures at the corners of the graft wherever possible). Aim: This paper describes a new suturing method, "the lingually-tied horizontal mattress contouring suture," for stabilization of CTGs with or without epithelialized collar at the recipient site, for use with papilla retention and sparing techniques to treat marginal tissue recessions. Methods and Material: The suturing technique is described in detail. It can be indicated for good number of root coverage cases, with additional objectives of gingival augmentation, specifically developed for papilla sparing and papillary buccal de-epithelialization recipient site preparations. Results: Over a period of last 16 years this suturing technique showed promising results in terms of graft stabilization and survival. The main advantage of this technique lies in the use of cost-effective nonabsorbable sutures that usually retain some amount of tension on the soft tissues longer. Conclusion: The primary objective of the suturing technique, per se, is to stabilize the CTG firmly along the contours of the root surface and to expedite a very close adaptation to the interdental soft tissues as well. The secondary objective of the article or publication is to disseminate the knowledge acquired through long periods of performance and observation for the benefit of the periodontal community as whole. Further validation is advocated.